COMMUNICATION STRATEGY FOR PRESERVING THE ERTUTUR TRADITION IN THE KARO BATAK COMMUNITY IN KUTALIMBARU DISTRICT - Br Tarigan, Revinta; Jailani, Muhammad (Journal Analytica Islamica, 2026)
The ertutur tradition is an important kinship communication system in the Batak Karo culture because it serves as a marker of social identity and a guideline for interactions between relatives. However, modernization and changes in social patterns have led to a decline in the understanding and practice of ertutur, especially among the younger generation. This study aims to analyze the communication strategies used in preserving the ertutur tradition in the Batak Karo community in Kutalimbaru District. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The results show that the preservation of the ertutur tradition is carried out through interpersonal communication strategies within the family, group communication in traditional activities, and participatory communication through cultural communities. The family acts as the initial agent of inheritance, traditional leaders act as the main director in the practice of ertutur at traditional events, while cultural communities strengthen the transmission of values through collective activities. This study also found that the main obstacles to preserving ertutur lie in the limited understanding of the younger generation, the weakening of traditional inheritance spaces, and the influence of modernization. The novelty of this study lies in explaining the preservation of ertutur as a multi-layered cultural communication process that occurs through families, customs, and local communities.